State-Space Modeling of a Class E2 Converter for Inductive Links - Luk, Patrick Chi-Kwong; Aldhaher, Samer; Fei, Wei-Zhong; Whidborne, James F. (IEEE, 2015)
This paper presents a state-space-based analysis of a Class E2 converter for wireless power systems based on a twocoil inductive link. The Class E2 converter consists of a 200-kHz Class E inverter as the primary coil driver and a voltage-driven Class E synchronous rectifier at the secondary coil of the inductive link. A piecewise linear seventh-order state-space model is used to calculate several parameters and values to achieve optimum switching operation of the Class E inverter and the Class E recti- fier. Simulation results are presented to compare the accuracy of the state-space modeling approach with the established analytical approach. For validation of the state-space analysis, an investigation of the influence of variation of coil alignment and load for a 20-W Class E2 converter prototype system is performed by means of a novel compensation method that maintains optimum switching conditions irrespective of variations. Experimental results are presented to confirm the accuracy of the state-space modeling approach over a wide range of operational conditions and the utility of the compensation method.
Keywords: DC-DC resonant converters; Inductive power transmission; Rectifiers